Industri Perfilman Bollywood: Evolusi Hiburan di Tengah Kemiskinan - Selvy Widuhung (Jurnal Komunikasi, 2008)
The victory of Slumdog Millionaire by winning 8 out of 10 nominations in Oscar 2009 is not only a recognition to Anil Kapoor, Dev Patel and Frieda Pinto's wonderful acting but also a proof that Bollywood movies can compete with Hollywood's. Through this glorious moment, the world's eyes are on to Bollywood, a movie industry which produces more than 8oo movies per year. This is such an amazing achievement above all the poverty and political issues that have been major problems in this second most-populated country in the world.